Agricultural potential of an industrial sewage sludge in compliance with CONAMA Resolution no. 375/2006 - Machado, Lívia Rodrigues Dias [UNESP]; Trannin, Isabel Cristina De Barros [UNESP] (Universidade Estadual de Londrina, 2015)
The agricultural use of sewage sludge is one of the best alternatives to disposal because of its potential as a plant fertilizer and soil conditioner. However, to be safe for agricultural use, the sewage sludge must be evaluated according to its physical, chemical, and biological properties and its origin. In Brazil, NBR 10.004/2004 is the standard that determines the classification of solid waste, and CONAMA Resolution 375/2006 defines the criteria for the agricultural use of sewage sludge. This study evaluated the agricultural potential of an aerobically digested industrial sewage sludge from the Serramar Dairy Cooperative in the city of Guaratinguetá, São Paulo. This sludge was classified as Class IIA waste according to NBR 10.004/2004 and displayed potential for agricultural use by falling within the limits in terms for heavy metals and pathogenic organisms established by Resolution 375/2006 as well as containing high levels of nutrients. To establish the sludge doses allowed for application to crops such as maize (annual) and Eucalyptus sp. (perennial) by the resolution, the amount of nitrogen available in the sludge and the amounts of this nutrient required by these crops were considered. The recommended sewage sludge doses for corn (8 Mg ha-1) and Eucalyptus sp. forestation (6 Mg ha-1) can meet the nitrogen and phosphorus needs of these crops but require supplementation with potassium mineral fertilizer.
Keywords: Agricultural recycling; Dairy sludge; Waste valuation